Kompetensi menelusur informasi melalui mesin pencari "Google" - Erika Erika (Al Maktabah, 2012)
Google is a search engine providing information with a high level of conformity to the requirements in comparison with other search engines. Using natural language index makes Google can accept all forms of queries that arc entered into the database. Despite the popular search engine has a design and search facilities as varied as simple and advanced searches, remain relevant information is obtained when a searcher has a good competence. Where the searcher has to understand the concept of information needs before conducting a search. Competence in searching through Google with a case study of Library Science Departement Student Adab and Humanities Faculty at UIN Syarif Hidayatullah Jakarta clone by observing the five informants to the understanding of the information needs, search strategies selection, strategies implementation, results assessment, and alternatives search if the results is not appropriate the needs. This study adapted the standard of competence ACRL Information Literacy Standards: The Information Literacy Competency Standards for Higher Education to provide indicators, outcomes, and coverage in the analysis. Kata kunci: Kompetensi Menelusur, Mesin Pencari Google, Literasi Informasi